2014
DOI: 10.1166/jnn.2014.10191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microstructure and Deformation Conditions on the Hot Formability of Ni–Ti–Hf Shape Memory Alloys

Abstract: Ingots of Ni-Ti-Hf shape memory alloys were prepared by vacuum arc re-melting. Isothermal hot compression tests were conducted at temperatures ranging from 700 to 1000 degrees C and at strain rates from 10(-2) s(-1) to 1.0 s(-1). A decrease in the Ni content below 50.2 at.% significantly deteriorated the hot workability due to the formation of a brittle second phase. Also, the low Ni content alloy showed poor workability when the temperature exceeded 900 degrees C. Additional compression tests were conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…TiNiHf alloys seem to be more attractive for wide practical application because they perform required mechanical and functional properties in combination with relatively low cost and greater stability of the operational characteristics as compared to TiNiZr alloys [ 15 ]. Therefore, to date, numerous studies of TiNiHf alloys revealed the main features of the formation of their structural state and properties [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Ternary TiNiHf alloys are usually divided into two groups, one with increased Ni content and one with reduced Ni content, similarly to binary TiNi SMAs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TiNiHf alloys seem to be more attractive for wide practical application because they perform required mechanical and functional properties in combination with relatively low cost and greater stability of the operational characteristics as compared to TiNiZr alloys [ 15 ]. Therefore, to date, numerous studies of TiNiHf alloys revealed the main features of the formation of their structural state and properties [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Ternary TiNiHf alloys are usually divided into two groups, one with increased Ni content and one with reduced Ni content, similarly to binary TiNi SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…Ternary TiNiHf alloys are usually divided into two groups, one with increased Ni content and one with reduced Ni content, similarly to binary TiNi SMAs. According to studies [ 16 , 17 , 18 , 19 , 20 ], alloys with low Ni content (less than 49.5 at.%) have insufficient technological plasticity due to the precipitation of the (Ti, Hf) 2 Ni-type phase. An increase in the Ni content leads to a decrease in the characteristic temperatures of martensitic transformations; therefore, in order to obtain a high-temperature state in the alloy, the content of Hf also should be increased [ 16 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation